Effect of the Single and Combined Use of Curcumin and Piperine on Growth Performance, Intestinal Barrier Function, and Antioxidant Capacity of Weaned Wuzhishan Piglets - Shi, Liguang; Xun, Wenjuan; Peng, Weiqi; Hu, Haichao; Cao, Ting; Hou, Guanyu (Frontiers in Veterinary Science, 2020)
This study was conducted to evaluate effects of the single and combined use of curcumin (CUR) and piperine (PIP) on performance, intestinal barrier function, and antioxidant capacity of weaned piglets. A total of 50 Wuzhishan piglets weaned at 35d of age were randomly assigned to five groups receiving a corn-soybean basal diet (CON), the basal diet supplemented with 50 mg/kg piperine, 200mg/kg curcumin (low-CUR), 200mg/kg curcumin+50mg/kg piperine (PIP+CUR) and 300mg/kg curcumin (high-CUR), respectively. The results showed that the feed/gain ratio (F/G) and plasma D-lactate and diamine oxidase activity (DAO) of the CUR+PIP and high-CUR groups were lower than those of the CON group (all P < 0.05), while the jejunum and ileum villus height, the villus height: crypt depth ratio, and the mRNA expression levels of occludin, claudin-1, and zonula occluden-1 in jejunal and ileal mucosa were higher in the CUR+PIP and high-CUR groups than in the CON group (all P < 0.05). Moreover, the piglets in the CUR+PIP and high-CUR groups had higher serum and intestinal mucosa activity of superoxide dismutase and glutathione peroxidase and lower malonaldehyde concentration than piglets in the CON group (all P < 0.05). The above parameters were not significantly different between the CUR+PIP and high-CUR groups (P > 0.05). In conclusion, the combination of CUR and PIP seemed to be as advantageous as high-CUR to piglets, but it was more effective than the single use of CUR and PIP. These data indicated that the basal diet supplemented with CUR+PIP or high-CUR could improve the intestinal permeability and suppress oxidative stress of weaned Wuzhishan piglets.